Magnetic properties of gadolinium substituted Bi2Te3 thin films - Li, S; Harrison, SE; Huo, Y; Pushp, A; Yuan, H; Zhou, B; Kellock, A; Parkin, S; Chen, Y; Hesjedal, T; Harris, J (2013)
Thin film GdBiTe3 has been proposed as a candidate material in which to observe the quantum anomalous Hall effect. As a thermal non-equilibrium deposition method, molecular beam epitaxy (MBE) has the ability to incorporate large amounts of Gd into Bi2Te3 crystal structures. High-quality rhombohedral (GdxBi1-x)2Te 3 films with substitutional Gd concentrations of x ≤ 0.4 were grown by MBE. Angle-resolved photoemission spectroscopy shows that the topological surface state remains intact up to the highest Gd concentration. Magnetoresistance measurements show weak antilocalization, indicating strong spin orbit interaction. Magnetometry reveals that the films are paramagnetic with a magnetic moment of 6.93 μB per Gd3+ ion. © 2013 AIP Publishing LLC.